Test Of The Effectiveness Of Giving Aloe Vera Extract In Reducing Cholesterol In Male Wistar Rats (Rattus Norvegicus) With Hypercholesterolemia - Henni Gustian; Hendy Million; Horas Rajagukguk (International Journal of Health and Pharmaceutical (IJHP), 2023)
Obesity prevention can be done with diet and exercise. Since plasma cholesterol levels are associated with diabetes, public interest in diabetes treatment in foods and herbal medicines has increased dramatically. This research wants to confirm and maximize topical plant treatment and diabetes medication benefits. This study employs a lab experiment. Aloe vera was examined for cholesterol-lowering capacity in hypercholesterolemic male Wistar rats (Rattus Norwegian) utilizing a pre-test-post-test control group. Aloe vera extract (Aloe vera) reduces cholesterol, body weight, and LDL in hypercholesterolemia-afflicted male Wistar white rats (Rattus norvegicus). One-way ANOVA test results show a significant value of 0.000 or less than 0.05. These statistics show a substantial difference between the control and treatment groups. This study's Post Hoc LSD test analysis indicated significance values of 0.000 and 0.018 or less than 0.05, indicating that all groups differed. Aloe vera extract reduces LDL significantly, and the group with a concentration of 4.5% reduced LDL levels more than the other groups in Wistar male white rats (Rattus norvegicus) with hypercholesterolemia.